If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5d + 11 = 8d + -7 Reorder the terms: 11 + 5d = 8d + -7 Reorder the terms: 11 + 5d = -7 + 8d Solving 11 + 5d = -7 + 8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8d' to each side of the equation. 11 + 5d + -8d = -7 + 8d + -8d Combine like terms: 5d + -8d = -3d 11 + -3d = -7 + 8d + -8d Combine like terms: 8d + -8d = 0 11 + -3d = -7 + 0 11 + -3d = -7 Add '-11' to each side of the equation. 11 + -11 + -3d = -7 + -11 Combine like terms: 11 + -11 = 0 0 + -3d = -7 + -11 -3d = -7 + -11 Combine like terms: -7 + -11 = -18 -3d = -18 Divide each side by '-3'. d = 6 Simplifying d = 6
| 3x-2y+5y-8x= | | -2(x-5)-3x=120 | | (57/2)x=26.8 | | -2.3-5x-4.1-3x=-7x+1.6 | | 2(3m-4)=8m-11 | | -2(-2)+4(4)=8 | | -3(2x+4-3-6x)-2=10x | | i+i+1+i+2=228 | | -5/2-1/4 | | .04(2-q)=0.2(q+7) | | 2xy=8+5y | | 4x+40=-24 | | -3=-32t-1 | | -5/2*-6 | | 35x-9=23x+90 | | s+3/1/2s+20=74 | | 2(x-4)+8=3x | | 9y-4x=9 | | 4(9y-5)=10+(3y+17)-40 | | -3/12 | | 2x+1/4=4x-2 | | 4/7=y+1/7 | | 5s-1=14 | | -12=q/3 | | 3/2+2m/3=23/6 | | z^2+4=9 | | -3/12=9/4 | | 3(-7-4x)=-153 | | 9y-15y=-18-24 | | x-6y=-19 | | 3(7-4x)=-153 | | -7k-6=15 |